(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
This paper examined the influence of emotional intelligence on disruptive behaviour among in-school adolescents in public secondary schools in Lagos State, Nigeria, and explored the effect of gender on these behaviours. Using a cross-sectional design, a total of 1001 adolescents (48.3% male, 51.7% female), aged 1218 years (M = 15.31; SD = 1.49), were sampled across nine public schools in four education districts. Participants completed the Schutte Self-Report Emotional Intelligence Test and the Conduct and Oppositional Defiant Disorder Scales (CODDS). Regression analysis revealed that emotional intelligence significantly and negatively predicted disruptive behaviour (β = –.21, p < .01), accounting for 4.5% of the variance. Male adolescents reported significantly higher disruptive behaviour than females (t = 5.36, p < .001). These findings emphasise the role of emotional intelligence in reducing disruptive tendencies and point to the importance of gender-sensitive behavioural interventions.